Impact of in vivo T cell depletion in HLA-identical allogeneic stem cell transplantation for acute myeloid leukemia in first complete remission conditioned with a fludarabine iv-busulfan myeloablative regimen: a report from the EBMT Acute Leukemia Working Party. Issue 1 (December 2017) - Rubio, Marie; D'Aveni-Piney, Maud; Labopin, Myriam; Hamladji, Rose-Marie; Sanz, Miguel; Blaise, Didier; Ozdogu, Hakan; Daguindeau, Etienne; Richard, Carlos; Santarone, Stella; Irrera, Giuseppe; Yakoub-Agha, Ibrahim; et al.
Abstract Background The impact of the use of anti-thymocyte globulin (ATG) in allogeneic stem cell transplantation performed with HLA-identical sibling donors following fludarabine and 4 days intravenous busulfan myeloablative conditioning regimen has been poorly explored. Methods We retrospectively analyzed 566 patients who underwent a first HLA-identical allogeneic stem cell transplantation with this conditioning regimen for acute myeloid leukemia in first complete remission between 2006 and 2013 and compared the outcomes of 145 (25.6%) patients who received ATG (ATG group) to 421 (74.4%) who did not (no-ATG group). The Kaplan-Meier estimator, the cumulative incidence function, and Cox proportional hazards regression models were used where appropriate. Results Patients in the ATG group were older, received more frequently peripheral blood stem cell grafts from older donors, and were transplanted more recently. With a median follow-up of 19 months, patients in the ATG group had reduced 2-year cumulative incidence of chronic graft-versus-host disease (GVHD) (31 vs. 52%, p  = 0.0002) and of its extensive form (8 vs. 26%, p  < 0.0001) but similar relapse incidence (22 vs. 27%, p  = 0.23) leading to improved GVHD and relapse-free survival (GRFS) (60 vs. 40%, p  = 0.0001). In multivariate analyses, the addition of ATG was independently associated with lower chronic GVHD (HR = 0.46, p  = 0.0001), improved leukemia-free survival (HR = 0.67, p  = 0.027), overall survival (HR = 0.65, p  = 0.027), and GRFS (HR = 0.51, p  = 4 × 10−5 ). Recipient age above 50 years was the only other factor associated with worse survivals. Conclusions These results suggest that the use of ATG with fludarabine and 4 days intravenous busulfan followed by HLA-identical sibling donor allogeneic stem cell transplantation for acute myeloid leukemia improves overall transplant outcomes due to reduced incidence of chronic GVHD without increased relapse risk.